Novel Deletion and Insertion Mutations Cause Splicing Defects, Leading to Severe Reduction in mRNA Levels of the A Subunit in Severe Factor XIII Deficiency - Izumi, Tomonori; Nagaoka, Utako; Saito, Tetsuo; Takamatsu, Junki; Saito, Hidehiko; Ichinose, Akitada (Thrombosis and Haemostasis, 1998)
In order to explore molecular mechanisms for factor XIII deficiency, a patient (Nagoya I) was examined at the DNA and RNA levels. Nucleotide sequence analysis of the patient’s DNA amplified by PCR revealed that he had a 20 bp deletion at the boundary of exon I/intron A, and an insertion of T in the invariant GT dinucleotide at the splicing donor site of exon IV/intron D. The presence of these heterozygous mutations was confirmed by restriction digestion of the amplified fragments of the proband and his parents. RT-PCR analysis demonstrated that only one kind of mRNA without exon IV was detected in Nagoya I, although its level was greatly reduced to less than 5% of normal. The other defective allele of the A subunit gene containing the 20 bp deletion was not detected. Thus, both mutations impaired normal processing of mRNA for the A subunit, resulting in his severe factor XIII deficiency.